Motor Abilities: Peculiarities of Strength Effort Assessment in Boys Aged 11-13 - O. V. Ivashchenko; M. O. Nosko; M. Cieślicka; D. A. Malyshev (OVS LLC, 2019)
Thepurposeofthestudyistodetermine the peculiarities of strength effort assessmentin boys aged 11-13. Materials and methods.The study participants were boys aged 11 years (n=22), 12 years (n=31), 13 years (n=33). The children and their parents were fully informed about all the features of the study and gave their consent to participate in the experiment. The paper used methods of scientific literature analysis, testing, methods of mathematical statistics. The study assessedthe right hand effort at 1/3, 1/2, 2/3 of the maximum. The assessment error was analyzed. To determine the peculiarities of strength effort assessment, the study used a t-test for paired observations and a t-test for independent samples. Results. The analysis of the ability for strength effort assessment in the boys aged 11 and 13 showed that there are no statistically significant differences between the boys of this age. The boysdemonstrate the best assessment ofeffortat2/3 of the maximum. There areno statistically significant differences in the levels of development of the hand maximum strength (p > 0.05). Thestudy has not found statistically significant differences in the levels of development of the ability for strength effort assessment in the boys aged 11-13(p > 0.05). The boys of this age demonstrate the best assessment ofeffortat2/3 of the maximum. A comparative analysis of the ability for strength effort assessment in the boys aged 12 and 13 did not reveal statistically significant differences (p > 0.05). The boys of this age demonstrate the best assessment ofeffortat2/3 of the maximum. The boys aged 11-13 show the best assessment of effort reproduction at2/3 of the maximum (p < 0.05). There is no statistically significant age-related dynamics in strength effortassessment in the boys aged 11-13. The correlationbetween the effort reproductionsat1/3, 1/2 and 2/3 of the maximum is not statistically significant. Conclusions.In the process of physical education of boys aged 11-13,special attention should be paid to the development of motor control ability as the component of coordination training of schoolchildren.